Assessment of width of attached gingiva in primary, mixed, and permanent dentition: Part - 2 - Shivani Singh; Kharidhi Laxman Vandana (Wolters Kluwer Medknow Publications, 2017)
Aim and Objective: The objective of this study was the arch and toothwise evaluation of attached gingiva width in primary, mixed, and permanent dentition. Materials and Methods: The study included 40 participants (22 males and 18 females) with 480 sites of an age range 4-25 years. Participants were divided into three groups - the primary dentition (4-6 years) mixed dentition (7-13 years) and adult dentition (16-25 years). The width of the attached gingiva was measured on the midfacial aspect of anterior teeth using calibrated University of North Carolina 15 periodontal probe. Results: Attached gingiva width (AGW) was measured archwise and toothwise in different dentition and overall data wise without differentiating archwise and toothwise. Gingival width increased with age and significantly higher in maxillary permanent dentition (3.4 ± 0.36). In maxilla, permanent central incisor (3.3 ± 0.3) and canine (3.5 ± 0.5) showed significantly higher gingival width than lateral incisor (2.5 ± 0.6) whereas other dentition showed nonsignificant difference. In all the dentition, variations were approximately similar in central incisor and canine. Conclusion: There was a greater overall width of attached gingiva in the maxilla than in the mandible. The AGW increases with age. It is greater in permanent dentition than primary and mixed dentition.